Analisis Etika Bisnis Islam dan UU Perlindungan Konsumen No. 8/1999 terhadap Jual Beli Account Game - Tubagus Farhan Fauzian; Siska Lis Sulistiani; Intan Nurrachmi (UNISBA Press, 2022)
Abstract. Buying and selling game accounts is rife on social media, this is used by game account sellers in the Rising Force Remastered buying and selling forum. The purpose of this study was to analyze Islamic business ethics and the Consumer Protection Law No. 8/1999 on buying and selling game accounts at the Rising Force Remastered buying and selling forum. The research method used is qualitative, with a normative juridical approach, the type of research data is library research, the source of research data comes from secondary data, data collection techniques use interviews and literature studies, data analysis techniques use descriptive qualitative. The results of this study are the practice of buying and selling game accounts is not in accordance with Islamic business ethics because the seller violates the provisions made by the game publisher, then buying and selling game accounts contains gharar related to the existence of the object, if the game service is closed then the game account buyer will lose so can eliminate the principle of willingness (an taradhin). The practice of buying and selling game accounts violates Article 4 letter c and Article 7 letter b in the Consumer Protection Law No. 8/1999. Abstrak. Jual beli Account game marak terjadi di media sosial, hal ini dimanfaatkan oleh penjual Account game di forum jual beli barang Rising Force Remastered. Tujuan penelitian ini adalah untuk menganalisis etika bisnis Islam dan UU Perlindungan Konsumen No.8/1999 terhadap jual beli Account game pada forum jual beli barang Rising Force Remastered. Metode penelitian yang digunakan adalah kualitatif, dengan pendekatan yuridis normatif, jenis data penelitian adalah penelitian kepustakaan (library research), sumber data penelitian berasal dari data sekunder, teknik pengumpulan data menggunakan wawancara dan studi pustaka, teknik analisis data menggunakan kualitatif deskriptif. Hasil penelitian ini adalah praktik jual beli Account game tidak sesuai dengan etika bisnis Islam karena penjual melanggar ketentuan yang telah dibuat oleh publisher game, kemudian jual beli Account game tersebut mengandung gharar terkait eksistensi objeknya, jika layanan game kelak ditutup maka pembeli Account game akan merugi sehingga dapat menghilangkan prinsip kerelaan (an taradhin). Praktik jual beli Account game tersebut melanggar Pasal 4 huruf c dan Pasal 7 huruf b dalam UU Perlindungan Konsumen No.8/1999.